الفكر والأسلوب في شعر عبد السلام المقدسي - حيدر, علي; فارس, عيسى; عبد القادر, ماهر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
عبد السلام المقدسي، شاعر وأديب من كبار أدباء الوعظ والتصوف في القرن السابع للهجرة. تشهد بذلك مؤلفاته التي ما يزال جُلُّها مخطوطاً، ينتظر أيدي المحققين والباحثين، لتخرجه إلى أيدي القراء والدارسين. لقد امتاز أدب المقدسي بغلبة الطابع التربوي، وكان الهدف الوعظي السمةَ المميزةَ لنتاجه شعراً ونثراً. وقد استطاع بفضل موهبته الأدبية، وقدراته البلاغية، أن يرتقي بأسلوبه الرمزي، ويجعله شفافاً يسهل فهمه على سامعيه وقرّائه، ويحقّق أهدافه الوعظية، وغاياته الإصلاحية الدينية. نعرض في هذه العُجالة شذراتٍ من إبداعاته الشعرية، كما نشير إلى الأساليب الفنية التي ابتكرها؛ كالتحدّث بلسان الحال، وتقمّص الشخصيات، فهو بحقٍ رائد هذين الفنين، وأول من أفرد لهما كتباً، ضمّنها حصيلة تجربته الصوفية، وحمّلها خلاصة آرائه في الكون والحياة والدين. Abdul Salam Al-makdssi is a poet, and one of the great writers of didactic and sophist literature in the seventh century (H.). His excellent writings, still in manuscripts, testify to this fact. His writings are distinct for their educational and psychological qualities. The didactic purpose is the main aspect of his literary production in general. However, his genuine poetic talent, his imagination, and rhetorical abilities, made his style so clear, and symbolic with special transparency and attractiveness. The poetry of Al-Makdssi was a truthful mirror of his own thoughts. In this paper, we present some aspects of his poetic production identifying its stylistic means like I personification and personification. He was a pioneer in this field and had books with ideas on sophism, life, the universe and religion.